PubMed Labs: an experimental system for improving biomedical literature search. (18th September 2018) - Fiorini, Nicolas; Canese, Kathi; Bryzgunov, Rostyslav; Radetska, Ievgeniia; Gindulyte, Asta; Latterner, Martin; Miller, Vadim; Osipov, Maxim; Kholodov, Michael; Starchenko, Grisha; Kireev, Evgeny; Lu, Zhiyong
Abstract: PubMed is a freely accessible system for searching the biomedical literature, with ∼2.5 million users worldwide on an average workday. In order to better meet our users' needs in an era of information overload, we have recently developed PubMed Labs (www.pubmed.gov/labs ), an experimental system for users to test new search features/tools (e.g. Best Match) and provide feedback, which enables us to make more informed decisions about potential changes to improve the search quality and overall usability of PubMed. In addition, PubMed Labs features a mobile-first and responsive layout that offers better support for accessing PubMed from increasingly popular mobiles and small-screen devices. In this paper, we detail PubMed Labs, its purpose, new features and best practices. We also encourage users to share their experience with us; based on which we are continuously improving PubMed Labs with more advanced features and better user experience.